THE PHILOSOPHY, CULTURE, CHANGING LIFESTYLE AND RURAL POVERTY IN THE 21ST CENTURY GHANA - Sebbeh, Bartholomew Johnson (European journal of philosophy, culture and religion, 2022)
Purpose: A cursory look at the lives of most people living in the rural areas of Ghana suggests that they are poor as compared to their counterparts living in the urban areas. The study aimed at investigating into the culture, philosophy, lifestyles and factors that have impacted negatively on the socio-economic situation that make the people living in the rural areas poor. Methodology: In order to obtain data on the causes of poverty among the rural people, the qualitative research approach was used for the study in which the observation method was employed to collect information from the elderly, youth, farmers, women, men, workers, illegal miners, traders, market women, etc. in some villages on their social lifestyles and economic activities. For effective and reliable outcome, unstructured interviews, surveys and investigations were used as tools to gather data. The use of unstructured interviews and conversations enabled majority of the sampled population who could not read nor write offer useful information. Findings: The study revealed that rural poverty is on the ascendency because most of the youth who serve as the work force migrate to the urban areas in search of jobs and better living conditions while a fraction of those who remained engage in illegal mining. The effect of this illegal activities has led to the degradation of arable lands, destruction of millions of acreages of cash/food crops and river bodies making agriculture, which is the backbone of the economy, very unsustainable. The attitude of majority of Ghanaians to time and work, especially in the public sector, leaves much to be desired. As a result, a lot of man-hours is rendered unproductive due to unpunctuality, religious and cultural activities. Unique contribution to theory and Practice and Policy: The outcome re-echoes the need for a policy direction on education that focuses on skill development and hands on experience to enable school leavers enter into entrepreneurship and be self-reliant so they will not be dependent on the limited government work. It will also make people come to the realization that only few people benefit from illegal mining but the harmful effects are universal and back government effort in fighting/curbing it. Government, Municipal/District Assemblies will see the need to provide amenities that rural communities lack, initiate intervention programmes for youth employment especially, in the rural areas to curtail rural-urban migration.